Creating a Circular City–An analysis of potential transportation, energy and food solutions in a case district. (January 2021) - Paiho, Satu; Wessberg, Nina; Pippuri-Mäkeläinen, Jenni; Mäki, Elina; Sokka, Laura; Parviainen, Tuure; Nikinmaa, Markus; Siikavirta, Hanne; Paavola, Martta; Antikainen, Maria; Heikkilä, Jouko; Hajduk, Petr; et al.
Highlights: Realistic transportation, energy and food alternatives are numerically analyzed. Business models for circular economy implementations are introduced. The regulatory outlook for circular cities is outlined. High-level circulation requires massive increases of production within city, which is unlikely. Holistic and multidisciplinary analysis is needed in realizing a circular city. Abstract: Circular economy plays a central role in cities on a strategical level. However, concrete circularity plans and actions remain rare. This paper examines how a city district could target circularity with transportation, energy and food solutions. The analysis is performed for an existing case district in a planning phase. The aim is to provide real concrete examples. Firstly, technological alternatives and their energy and carbon emissions are analyzed numerically. Secondly, service solutions for each technology are suggested. Thirdly, relevant regulations are framed. In the analyzed district, high-level circulation of urban streams is unlikely to occur. Almost carbon-free transportation is possible, resulting in extensive increase in local electricity demand. Locally produced biogas would contribute about 20 % of the gas demand of the most advanced transportation scenario. None of the several energy production alternatives would lead to local energy self-sufficiency. Waste heat recovery from a data center and a wastewater treatment plant could supply 58 % of the heat demand. 6 % of the food consumed could be produced locally. The paper highlights the importance of considering interlinkages between different streams and sectors, revealing the complexity of a circular city. The analysis demonstrates that circularity in this district is possible, but requires multidisciplinary analysis.